2021
DOI: 10.1177/01640275211027281
|View full text |Cite
|
Sign up to set email alerts
|

Marital Status, Marital Transitions, and Sleep Quality in Mid to Late Life

Abstract: This study aimed to understand how marital status and marital transitions were related to sleep quality in mid to late life and whether these findings differed by gender. Data from 2,872 participants 50–74 years old from the ORANJ BOWLSM, a longitudinal panel study in New Jersey, were used. Marital status and sleep quality were examined in two waves that were approximately 10 years apart. Individuals in a significant romantic relationship and women had worse sleep quality than those in other marital status gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…[44] The study participants who had unstable marriages were associated with poor sleep quality compared to those who had stable marriages (AOR = 3.758; 95% CI: 1.151-12.277). This is in agreement with the studies conducted in New Jersey, [45] Saudi, [46] and Yunnan, China. [47] Lee et al found that marital quality is positively correlated with sleep quality.…”
Section: Discussionsupporting
confidence: 93%
“…[44] The study participants who had unstable marriages were associated with poor sleep quality compared to those who had stable marriages (AOR = 3.758; 95% CI: 1.151-12.277). This is in agreement with the studies conducted in New Jersey, [45] Saudi, [46] and Yunnan, China. [47] Lee et al found that marital quality is positively correlated with sleep quality.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, individuals who were divorced or currently married had better sleep quality score than those who were never married. A previous study in the USA observed that individuals transitioning into marriage had improved sleep quality while those becoming divorced had subsequent risk of poor sleep quality [ 39 ]. This study found higher odds of having sleep problems among those with DM and other multimorbid conditions, a finding consistent with that observed among individuals with similar morbidity profile in other LMICs [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Results also indicate that married individuals are more efficient sleepers, use fewer medications, and have less daytime dysfunction than unmarried individuals, suggesting that despite poor overall sleep quality scores, married military personnel can compensate for the demands of daytime work by improving their sleep efficiency. Another possible explanation for the results is that sleeping with a spouse who develops sleep apnea may interfere with the individual’s sleep ( 20 ). The lack of investigation of the physical condition of the spouse in this study warrants caution in the interpretation of the results.…”
Section: Discussionmentioning
confidence: 99%